Elderly People’s Expectations from a Housing Environment in the Context of Aging in Place: The Case of Afyonkarahisar - Muhammet Keskin; Üzeyir Yasak (Coğrafya Dergisi)
Global demographic changes are being experienced the most concretely in the 21st century. Academic studies on older people’s socioeconomic, cultural, and spatial needs have become increasingly important. This study aims to determine what elderly individuals aged 65 or older expect from the residential setting in Afyonkarahisar city center. To test the hypotheses, the study has applied a questionnaire to 374 elderly individuals in the sample area determined in the city center. The study uses explanatory factor analysis and difference tests, and the results of the research have identified that individuals aging in place care about the characteristics of their residential environment, such as accessibility, proximity to aging-related services, socioeconomic structure, environmental factors, and social networks and relationships. Education level and monthly income are important variables affecting what is expected from the residential environment. Older people’s expectations regarding accessibility to various services, socioeconomic structure, social networks and relationships in the residential environment have been shown to vary based on their education levels. Older people’s perspectives on social networks and relationships have also been shown to differ based on their monthly income.